2012
DOI: 10.1073/pnas.1201632109
|View full text |Cite
|
Sign up to set email alerts
|

Role of genes linked to sporadic Alzheimer’s disease risk in the production of β-amyloid peptides

Abstract: Alzheimer's disease (AD) is characterized by the presence of toxic protein aggregates or plaques composed of the amyloid β (Aβ) peptide. Various lengths of Aβ peptide are generated by proteolytic cleavages of the amyloid precursor protein (APP). Mutations in many familial AD-associated genes affect the production of the longer Aβ42 variant that preferentially accumulates in plaques. In the case of sporadic or late-onset AD, which accounts for greater than 95% of cases, several genes are implicated in increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 37 publications
2
73
1
Order By: Relevance
“…This is in contrast to similar knockdown studies of various LOADrelated genes (e.g. BIN1, Clustrin, and CD33) where no effect on APP processing was observed, but ABCA7 was not examined in this particular investigation (37). In the current study, loss of ABCA7 in cells overexpressing APPSw resulted in increased ␤-cleavage products and A␤ secretion.…”
Section: Discussioncontrasting
confidence: 53%
“…This is in contrast to similar knockdown studies of various LOADrelated genes (e.g. BIN1, Clustrin, and CD33) where no effect on APP processing was observed, but ABCA7 was not examined in this particular investigation (37). In the current study, loss of ABCA7 in cells overexpressing APPSw resulted in increased ␤-cleavage products and A␤ secretion.…”
Section: Discussioncontrasting
confidence: 53%
“…It is conceivable that the increased accumulation of amyloid beta peptides in sporadic AD results from increased expression of APP gene and / or increased processing of the APP gene product in the amyloidogenic pathway by means of β and γ secretases and / or decreased catabolism and clearance of the peptides from the brain. In case of familial AD, the mutations in APP, PS1 or PS2 gene may lead to similar effects with accumulation of amyloid beta peptides in the brain, and the 'Amyloid Cascade Hypothesis' as the pathogenic mechanism of AD has gained huge support from identification of these familial AD mutation [29,31]. The other suggested mechanism in AD pathogenesis emphasizes the neuronal and synaptic dysfunctions caused by the abnormal accumulation of phosphorylated tau protein (tauopathy) [32,33].…”
Section: Pathogenesis Of Alzheimer's Diseasementioning
confidence: 99%
“…Similarly, also CLU and PICALM had been shown to enhance the transport of Aβ across the blood-brain barrier and the bloodcerebrospinal fluid barrier [12] [13] [14] [15]. In line with the notion that LOAD genes do not specifically affect Aβ production, a recent study did not detect specific effects of the knockdowns of several LOAD susceptibility genes on Aβ levels or the 42:40 ratio in a HeLa cell APP overexpression system [1].…”
Section: Introductionmentioning
confidence: 54%
“…While genome-wide association studies (GWAS) have identified certain genetic risk factors associated with late-onset AD, the mechanisms through which they contribute to the pathogenesis are still elusive. Previously, using a HeLa cell model of Aβ production, it was shown that, in contrast to the early-onset AD causing mutations, knockdown of late-onset AD susceptibility genes did not specifically affect the Aβ 42 :Aβ 40 ratio [1]. To validate these findings in a neuronal setting without any overexpression of APP, here we re-addressed the role of six late-onset AD risk genes (APOE, BIN1, PICALM, CLU, PRNP and CST3) in the regulation of γ-secretase mediated APP processing in wild-type mouse primary neurons by analyzing Aβ x-40 and Aβ x-42 .…”
mentioning
confidence: 99%